(untitled) (Bangladesh Journal of Child Health, 2013)
Objects: A hospital based descriptive study was carried out among under-5 children suffering from severe protein-energy-malnutrition (PEM) Methodology: This was a descriptive analytical study conducted during June 2002 to May 2003 in three purposively selected hospitals of Dhaka city, Bangladesh. Results: Mean±SD age of the children was 15.1±10.9 months, majority being under three years (91.5%), 47.2% were female, and 51% did not receive or complete immunization according to their age. No significant age and sex difference was found among the admitted children in different hospitals. Most of their parents were illiterate (mothers 71%, fathers 56%) with low family income and social status. Marasmus cases were 61%, followed by kwashiorkor 25% and marasmic kwashiorkor 14%. The children were managed broadly according to standard protocol based on the guideline of World Health Organization but adopted/modified by the individual hospitals. Overall outcome of the patients were: recovery 62.4%, default 21.4%, death 13.7% and transfer 2.6%. Mean duration of hospital stay was 14.2±9.9 (ranging from 0 to 59) days. Recovery rate was better among male (67.3%) than female (56.8%) children, p=0.033. Default rate was higher among female (27.3%) than male (16.1%) children, p=0.007. Case fatality rate was highest (40%, p=0.001) in children suffering from septicaemia. Conclusion: Evidences of faulty case management practices viz. over use of intravenous fluids and blood transfusion, inappropriate diets, less use of micronutrients, incorrect antibiotics were observed occasionally in all the three hospitals. Updated and comprehensive treatment guidelines need to be implemented, and every hospital should review its own clinical management procedures and performance with a view to improving practice. DOI: http://dx.doi.org/10.3329/bjch.v37i1.15345 BANGLADESH J CHILD HEALTH 2013; VOL 37 (1) : 5-13